Structural and magnetic properties of nanocrystalline equi-atomic spinel high-entropy oxide (AlCoFeMnNi)3O4 synthesised by microwave assisted co-precipitation technique - Shaw S.K.; Gangwar A.; Sharma A.; Alla S.K.; Kavita S.; Vasundhara M.; Meena S.S.; Maiti P.; Prasad N.K. (My University, 2025)
Single phase equi-atomic (Al0.2Co0.2Fe0.2Mn0.2Ni0.2)3O4 high-entropy oxide (HEO) having spinel structure was synthesised employing simple and cost effective microwave assisted co-precipitation technique, followed by calcination at 500 °C. The material obtained was highly crystalline and stable at higher temperatures. The uniformity in elemental distribution was apprehended through STEM-EDS elemental mapping. The X-ray photoelectron spectroscopy confirmed +3 ionic state for Fe and Al, while other elements oxidised to higher ionic states to maintain charge neutrality. Ferrimagnetic behaviour was confirmed for the obtained HEO through magnetic characterisations. © 2021 Elsevier B.V.